Pembuatan Evoting dengan Model Multi Vote Berdasarkan Kategori Menggunakan Hashing SHA-256: Studi Kasus SMK Plus YSB Suryalaya - Tatang Nugraha (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
Voting at SMK Plus YSB Suryalaya has traditionally been carried out manually, resulting in a time-consuming process that is prone to errors. Therefore, to improve the efficiency and accuracy of the election process, an online voting system is needed. This research aims to develop a web-based E-Voting system with a Multi-Vote model, allowing voters to vote for multiple candidates across different election categories. This system is designed to simplify the election process at the school, with features such as candidate registration, voter registration, real-time voting, and automatic processing and tabulation of election results. The system was tested using Black Box Testing to ensure its functionality and security, and the results show that the system performs well and meets user requirements. With this system, it is expected that the election process at SMK Plus YSB Suryalaya can be carried out more efficiently, transparently, and with fewer errors.